El verdadero promotor detrás del éxito Europeo (2019)
In this article, it is a critica! analysis of the documented reality about the events that took place, during the period of the conques! and colonization of the American continent, by the European settlers, emphasizing the phenomena that they unleashed, not only in the Americas, if not, taking into account the repercussions that in social, economic and political relations, transfarmed from the dynamics of the continents affected by this series of events, trying to understand the roles of the American and African continent, in the conditions imposed by the conquerors as the dominan! actors of this time, to establish a series of reflections that will include the most relevant aspects, both socially and economically, in the same way, phenomena linked to the so-called encounter are emerging, Between two worlds, which allows establishing the bases far future evaluations on the theme of the conques! and the colony, putting on the table, a series of events, that the history books do not usually tell, leaving aside the premise, the discovery of America. , and to expose the consequences and repercussions left by this period, far the history and development of the Latin American communities, which are still under the control and domination of capital, of which they are the great economic powers of the world, mostly of European descent.